The life we bury - Eskens, Allen, 1963- (Amherst, NY : Seventh Street Books, an imprint of Prometheus Books, 2014)
College student Joe Talbert has to interview a stranger and write a brief biography of the person. At a nearby nursing home, he meets Carl Iverson, and soon nothing in Joe's life is ever the same. Iverson is a dying Vietnam veteran--and a convicted murderer. Joe, along with his skeptical female neighbor, throws himself into uncovering the truth.
Keywords: Mystery fiction; Murderers -- Fiction; College students -- Fiction